Descriptive study of the top spin rotation and of the striking top spin of expert table tennis players - Poizat, G.; Thouvarecq, R.; Seve, C. (Journal of Sports Sciences, 2006)
Introduction: The aim of this study was to describe two strokes : the top spin rotation and the striking top spin. The study includes an analysis of the movement, and the study of relative and temporal structures such as those developed in the centro-peripheral theory (Schmidt R.A., 1975, Psychological Review, 82(4), 225-260). The goals were to create patterns of profiles, to create a 2D representation of the two strokes, and to study the motor control. The hypothesis being that it was in reality a gesture with variations which means that these two gestures belong from the same generalized motor program (PMG).